1964
DOI: 10.1111/j.2042-7158.1964.tb07509.x
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal activity of chloroxylenol in aqueous solutions of cetomacrogol

Abstract: The bactericidal activity of chloroxylenol in water and in solutions of the non‐ionic surface‐active agent cetomacrogol is shown to be related to the degree of saturation of the system, expressed as a Saturation Ratio, which is the ratio of the amount of chloroxylenol present to its solubility. A saturated solution of chloroxylenol in water is shown to have the same bactericidal activity as saturated surfactant solutions containing up to 100 times as much chloroxylenol. It is apparent that bactericidal activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1964
1964
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Allawala and Reigelman showed that a governing factor of efficacy of a phenolic agent in surfactant solution was the % saturation of the phenolic (which is an index of its thermodynamic activity) in the solution, and not simply its total concentration; the two can be very different depending on the mode of solubilization. Mitchell [5] extended this approach to chloroxylenol, a phenolic biocide. Mitchell showed that a saturated solution of chloroxylenol in water had the same bactericidal activity as saturated surfactant solutions of chloroxylenol containing up to 100-fold greater amounts of the biocide.…”
Section: Introductionmentioning
confidence: 99%
“…Allawala and Reigelman showed that a governing factor of efficacy of a phenolic agent in surfactant solution was the % saturation of the phenolic (which is an index of its thermodynamic activity) in the solution, and not simply its total concentration; the two can be very different depending on the mode of solubilization. Mitchell [5] extended this approach to chloroxylenol, a phenolic biocide. Mitchell showed that a saturated solution of chloroxylenol in water had the same bactericidal activity as saturated surfactant solutions of chloroxylenol containing up to 100-fold greater amounts of the biocide.…”
Section: Introductionmentioning
confidence: 99%
“…Bean & Berry (1948, 1951, however, claimed that the bactericidal activity of benzylchlorophenol in aqueous solutions of potassium laurate was related to the concentration of the benzylchlorophenol in the micelles of potassium laurate and was independent of the overall concentration in the solution. Mitchell (1964) found the bactericidal activity of chloroxylenol in water and in solutions of the nonionic surface active agent cetomacrogol to be dependent on the degree of saturation of the system expressed as a saturation ratio i.e. the ratio of the amount of dissolved chloroxylenol present to its saturation solubility.…”
mentioning
confidence: 99%
“…the ratio of the amount of dissolved chloroxylenol present to its saturation solubility. The work of Bean & Berry (1948, 1951, Pisano & Kostenbauder (1959) and Mitchell (1964), suffers from the imprecision associated with determinations based on quanta1 data and also, in the case of the last, that binding data were estimated from microbiological measurements in systems where other ingredients might interfere with the degree of binding.…”
mentioning
confidence: 99%
“…UMEROUS reports have appeared in recent N years concerning the inactivation of various antibacterial preservatives when in the presence of pharmaceutically employed materials such as vegetable gums (1)(2)(3)(4)(5) and nonionic surfactants (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Several of these studies have included data and hypotheses on the nature of the interactions between phenolic compounds and polymers, as polyethylene glycol and polysorbate 80 (13-15).…”
mentioning
confidence: 99%
“…Several of these studies have included data and hypotheses on the nature of the interactions between phenolic compounds and polymers, as polyethylene glycol and polysorbate 80 (13-15). Such interactions have resulted in pharmaceutical incompatibilities (19,20) or in the reduction of antibacterial activity (17,21,22). In view of the possibility of preservative interactions with other formulative materials, it is recognized that chemical assays of preservative concentration may not always be a true measure of effective antimicrobial concentration (22).…”
mentioning
confidence: 99%